1996
DOI: 10.1111/j.1476-5381.1996.tb15690.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effects of 7‐nitroindazole in rodents with reflex epilepsy may result from L‐arginine accumulation or a reduction in nitric oxide or L‐citrulline formation

Abstract: To investigate the role of nitric oxide in epilepsy we have studied the effects of agents which affect nitric oxide synthesis in sound‐induced seizures in DBA/2 mice and in genetically epilepsy‐prone (GEP) rats. The neuronal selective nitric oxide synthase inhibitor, 7‐nitroindazole (7‐NI) is anticonvulsant in these models with ED50 values against clonic seizures in mg kg−1 i.p. (times following injection) of: 74 (+0.25 h), 120 (+1 h) in DBA/2 mice, and 56 (+0.25 h), 42 (+0.5 h), 36 (+1 h), 28 (+2 h), 38 (+4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…If the relationship between NOS inhibition and 7-NI concentration is ascertained, it becomes possible to design dosing regimens that produce a specific degree of NOS inhibition. [21]. These studies have relied on empirical dosing of 7-NI due to a lack of pharmacokinetic and pharmacodynamic information.…”
Section: Discussionmentioning
confidence: 99%
“…If the relationship between NOS inhibition and 7-NI concentration is ascertained, it becomes possible to design dosing regimens that produce a specific degree of NOS inhibition. [21]. These studies have relied on empirical dosing of 7-NI due to a lack of pharmacokinetic and pharmacodynamic information.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was demonstrated that L-arginine, at a dose of 300 mg (i.c.v. ), was anticonvulsant against soundinduced seizures in DBA/2 mice and genetically epilepsyprone rats (18).…”
Section: Discussionmentioning
confidence: 99%
“…The protective action of 7-NI combined with CBZ or PB against amygdala-kindled seizures was not reversed by L-arginine, so the involvement of NO in this particular interaction does not seem probable. It is also unlikely that the ineffectiveness of L-arginine could be associated with the mechanism postulated by Smith et al (6) for sound-induced seizures. Actually, in amygdala-kindled seizures in rats, L-arginine was ineffective in doses up to 500 mg/kg, and the anticonvulsant effects of 7-NI and an AED were not further enhanced by the NO donor.…”
Section: Discussionmentioning
confidence: 94%